The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.visres.2009.02.007
|View full text |Cite
|
Sign up to set email alerts
|

In visual search, guidance by surface type is different than classic guidance

Abstract: Visual search for targets among distractors is more efficient if attention can be guided to targets by attributes like color. In real-world search, we guide attention using information about surfaces. (e.g., paintings are on walls). We compare “classic” color guidance to surface guidance in “scenes” of cubes. When a target can lie on one of many surfaces, color guidance is effective but surface guidance is not (Exp. 1-3). Surface guidance works when cued surfaces are coplanar (Exp. 4) or few in number (Exp. 5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 37 publications
3
3
0
Order By: Relevance
“…Participants missed 20-30% of the targets in these experiments, a much higher rate than those typically observed in lab based visual search experiments 7 . Recent work has found that a similar percentage of errors has been observed in Low Prevalence (LP) visual search tasks where the target only appears rarely (approximately 1-2% of the time, Wolfe et al, 2005, Fleck & Mitroff, 2007, Kunar et al, 2010, Rich et al, 2008, Russell & Kunar, 2012, and Van Wert et al, 2009. In these LP 7 When the target was a unique blinking item (Experiment 6) or a unique moving item (Experiment 7), however, miss errors were relatively low, following the trend found in the RT data.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Participants missed 20-30% of the targets in these experiments, a much higher rate than those typically observed in lab based visual search experiments 7 . Recent work has found that a similar percentage of errors has been observed in Low Prevalence (LP) visual search tasks where the target only appears rarely (approximately 1-2% of the time, Wolfe et al, 2005, Fleck & Mitroff, 2007, Kunar et al, 2010, Rich et al, 2008, Russell & Kunar, 2012, and Van Wert et al, 2009. In these LP 7 When the target was a unique blinking item (Experiment 6) or a unique moving item (Experiment 7), however, miss errors were relatively low, following the trend found in the RT data.…”
Section: Discussionsupporting
confidence: 57%
“…In contrast there was little change in sensitivity (Russell & Kunar, 2012, and Van Wert et al, 2009. Given that the miss rates here were similar in numerosity to that of LP experiments one could suggest that a similar process was occurring.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations